Integration of Landscape Details (Hong Kong : Tran Art, 2011)
This book selects more than 6000 pictures about landscape details of property landscape, park, wet land and tourism area. Most of the pictures are taken by our photographers like Xiao Kaixiong, who initiates a special trip to Xian in China and regions in Japan and America. These pictures are latest and original as well. According to modern landscape elements, all the pictures are categorized into 13 categories which are landscape planning, landscape early expansion figure, plaza, yard, waterscape, greening, road, mat formation, landscape ornament, architectural ornament, installation landscape and landscape lighting. In every category, there are secondary, third or even fourth subdivisions, making the categorization as detailed as possible and contain as much information as it can. Compared with other books on landscape details, this book simultaneously contains three categories, namely drawing of landscape planning, landscape early expansion figure and picture of landscape aerial view. This is also a highlight of this book.
Keywords: Landscape architects